Colonic Interposition in a Woman with Attenuated Familial Adenomatous Polyposis: Does the Location of the Colon Affect Polyp Formation? - Melanie D Beaton; Brian Taylor; David Driman; Peter Ainsworth; Paul C Adams (Canadian Journal of Gastroenterology)
Attenuated familial adenomatous polyposis (AFAP) is a rare but well-established cause of colorectal carcinoma and multiple polyps. The present paper describes a case of a woman diagnosed with colorectal cancer at 34 years of age and subsequently found to have AFAP by genetic testing. During infancy, the patient underwent surgical correction of esophageal atresia with colonic interposition. While she had developed adenomatous polyps in her native cecum, there was no evidence of polyps or cancer in the segment of large intestine interposed between her upper esophagus and stomach. Therefore, various environmental differences between the upper and lower gastrointestinal tract may play a role in the expression of AFAP phenotype.